How to diagnose, treat and prevent from hospital-acquired and ventilator-associated pneumonia? - Babiak, Rafał; Bajak, Karolina; Czuchryta, Paulina; Domańska, Anastazja; Gawęda, Agnieszka; Grabek, Agata; Rutkowska, Julia; Rzęsa-Tokarczyk, Żaneta; Skorek, Klaudia; Urbańczyk, Agnieszka (Journal of Education, Health and Sport, 2023)
Introduction and purpose: hospital-acquired pneumonia and ventilator-associated pneumonia are common risk factors for morbidity and mortality. They are difficult to diagnose and treat due to the large number of factors that may contribute to the deterioration of the clinical condition of critically ill patients. In this article, the authors summarize the diagnosis, treatment and prevention of these diseases based on current guidelines, the latest research and other scientific works. Material and metod: sources available in the PubMed database were analyzed using the following keywords: "pneumonia", "hospital-acquired pneumonia", "ventilator-associated pneumonia", "HAP", "VAP", publications related to the subject of the work were selected and used. Conclusion: A patient with HAP or VAP should undergo non-invasive testing such as blood and sputum cultures and nasal swabs to isolate the pathogen responsible for the infection and to adjust antibiotic therapy. The procalcitonin level can be used in conjunction with the clinical assessment to assess the adjustment of the duration of treatment. Patients with HAP or VAP who are immunocompromised, haemodynamically unstable, or cannot be sampled from the lower respiratory tract for microbiological testing should be treated with empiric antibiotics based on individual risk factors and antibiotic resistance.